Elegant Automation Frameworks with Python and Pytest - Blair, Brandon (Packt Publishing, 2020)
Leverage pytest's fast, scalable, and professional-grade framework design to build and run automated test suites like a pro About This Video Become proficient in automated testing using pytest Create a well-organized, scalable test framework on a professional level Find out how fixtures can eliminate up to 80% of code in a bloated codebase In Detail Python is one of the most popular programming languages in the world, with its demand increasing by the minute. Pytest - one of the most actively maintained testing frameworks in the industry - provides an incredible set of tools for faster, less stressful testing. In this course, you'll learn how to eliminate boilerplate setup and teardown code, run multiple tests simultaneously, and track your test run history to identify slow or problematic tests. Beginning with a brief introduction and a step-by-step setup of pytest, this course will walk you through each session. You'll discover what makes a good framework, and, more importantly, what makes a bad one. As you advance, you'll learn how to use test searching to avoid cumbersome test suites, and how fixtures can eliminate up to 80% of code in case of code bloat. This interactive course is also equipped with information-rich videos to help you grasp the concepts with ease. By the end of this course, you'll be ready to build high-performance, well-organized, scalable test frameworks on the professional level.